2012
DOI: 10.1016/j.jpor.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of nanostructure on titanium surface modified by chemical processing at room temperature

Abstract: In conclusion, these data suggest that titanium implants modified by the application of nanostructures promote osteogenic differentiation, and may improve the biointegration of these implants into the alveolar bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…30 The nanotopography of nanonetwork structures with TNS nanofeatures is affected by temperature, treatment time, and alkaline concentration. 20,[31][32][33] The objectives of the present study were twofold: first, we aimed to investigate the changes in TNS, such as roughness, wettability, and surface structure induced by various alkaline concentrations (2.5, 5.0, 7.5, 10.0, and 12.5 M), and second, we aimed to evaluate the influence of such modified nanonetwork structures with TNS nanofeatures, with different alkaline concentrations, on the osteogenic differentiation of rat BMMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…30 The nanotopography of nanonetwork structures with TNS nanofeatures is affected by temperature, treatment time, and alkaline concentration. 20,[31][32][33] The objectives of the present study were twofold: first, we aimed to investigate the changes in TNS, such as roughness, wettability, and surface structure induced by various alkaline concentrations (2.5, 5.0, 7.5, 10.0, and 12.5 M), and second, we aimed to evaluate the influence of such modified nanonetwork structures with TNS nanofeatures, with different alkaline concentrations, on the osteogenic differentiation of rat BMMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, we demonstrated that TiO 2 nanotubes and TNSs could be formed on titanium metal surfaces by treatment with a 10 M NaOH aqueous solution at 30°C, and we used this method to prepare TNS-modi ed disks. Komasa et al [8] suggested that TNSs on titanium surfaces can be applied to control the osteogenic di erentiation of bone marrow cells and enhance mineralization. Our results demonstrated that TNS-modi ed titanium disks were more hydrophilic and showed uniquely enhanced wettability in comparison with unmodi ed disks.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [8], we showed that TNSs created by compound processing enhance the osteogenic separation of rodent bone marrow (RBM) cells. e surface properties and structural characteristics of materials play an important role in protein and cell adsorption behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that treatment with NaOH aqueous solution produces a rough, nanoscale surface. A previous study reported that TNS produced via chemical processing promoted osteogenic differentiation of rat bone marrow (RBM) cells 4,5) . The surface properties and structures of materials play important roles in the adsorption of proteins, which might influence cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…24(3):257 -266, 2015 reports that NaOH treatment leads to the formation of a Ti-O-Na titanate layer on the Ti surface 4,6) . V is known to exhibit biological toxicity, so it is interesting that this component was undetected on the TNS-modified titanium surface.…”
Section: Introductionmentioning
confidence: 99%